Integration of Digital Technology to E-Commerce Transactions as a Basis for Central Digital Currency Development - Wahyudi, Heru; Lestari, Winda Rika; Sunarmi, Sunarmi; Leny, Sandra Mei (International Journal of Economics and Financial Issues, 2024)
This study analyses the effect of digital technology integration on e-commerce transactions as a basis for Central Digital Currency (CBDC) development. By taking into account independent variables such as the number of internet users and the number of mobile device users, this study identifies the correlation between the development of digital technology and the adoption of e-commerce transactions with the potential implementation of Central Digital Currency (CBDC). Using the panel data regression analysis method, the results show a significant relationship between digital technology and an increase in the volume of e-commerce transactions, which can accelerate the development of Central Digital Currency (CBDC). The findings also strengthen the argument that the increased use of digital technology can be an important indicator in the development of digital currencies by central banks. This study suggests the need for more comprehensive regulations in support of the digital ecosystem and infrastructure readiness for Central Digital Currency (CBDC) in the future.